An observational study on risk of secondary cancers in chronic myeloid leukemia patients in the TKI era in the United States - Kumar, Vivek; Garg, Mohit; Chaudhary, Neha; Chandra, Abhinav Binod (PeerJ, 2018)
Introduction The treatment with tyrosine kinase inhibitors (TKIs) has drastically improved the outcome of chronic myeloid leukemia (CML) patients. This study was conducted to examine the risk of secondary cancers (SCs) in the CML patients who were diagnosed and treated in the TKI era in the United States. Methods The surveillance epidemiology and end results (SEER) database was used to identify CML patients who were diagnosed and received treatment during January 2002–December 2014. Standardized incidence ratios (SIRs) and absolute excess risks (AER) were calculated. Results Overall, 511 SCs (excluding acute leukemia) developed in 9,200 CML patients followed for 38,433 person-years. The risk of developing SCs in the CML patients was 30% higher than the age, sex and race matched standard population (SIR 1.30, 95% CI: 1.2–1.40; p < 0.001). The SIRs for CLL (SIR 3.4, 95% CI: 2–5.5; p < 0.001), thyroid (SIR 2.2, 95% CI: 1.2–3.5; p < 0.001), small intestine (SIR 3.1, 95% CI: 1.1–7; p = 0.004), gingiva (SIR 3.7, 95% CI: 1.2–8.7; p = 0.002), stomach (SIR 2.1, 95% CI: 1.1–3.5; p = 0.005), lung (SIR 1.4, 95% CI: 1.1–1.7; p = 0.006) and prostate (SIR 1.3, 95% CI: 1.02–1.6; p = 0.026) cancer among CML patients were significantly higher than the general population. The risk of SCs was higher irrespective of age and it was highest in the period 2–12 months after the diagnosis of CML. The risk of SCs in women was similar to that of the general population. Conclusion CML patients diagnosed and treated in the TKI era in the United States are at an increased risk of developing a second malignancy. The increased risk of SCs in the early period after CML diagnosis suggests that the risk of SCs may be increased due to the factors other than TKIs treatment.
Keywords: CML; Tyrosine kinase inhibitors; TKI; SEER; SIR; Relative risk; Secondary cancers; Population based; Observational; Excess risk